The green infrastructure of a highly urbanized Neotropical city: the role of the urban vegetation in preserving native biodiversity - Pena, João Carlos Castro; Magalhães, Danilo Marques; Moura, Ana Clara Mourão; Young, Robert John; Rodrigues, Marcos (Revista da Sociedade Brasileira de Arborização Urbana, 2016)
We mapped and described the composition of the urban vegetation that comprises the green infrastructure of a highly urbanized Neotropical city, and discussed how it can be used to preserve and maintain urban biodiversity. Almost half of our study area is occupied by 12 types of arboreal and herbaceous vegetation, composed mostly of urban parks, gardens and street trees. Forty-one percent of the almost 90,000 street trees are composed of 10 species with only 4 native species. These results show that this urban landscape is highly heterogeneous and has a great potential for biodiversity conservation. However, management strategies are needed, such as better planning of the urban forestry. This study is the first step towards a better understanding of how this landscape influences local biodiversity, and can be used as a management tool to increase urban resilience and functionality.